2018
DOI: 10.1002/pd.5222
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fetal surgery techniques to close a spina bifida defect in the fetal lamb model: A systematic review

Abstract: The experimental literature on prenatal SB closure underscores the lack of standardization. At present, there is animal experimental evidence that a 2-layer closure by hysterotomy is safe and effective. This technique is currently clinically used in a subset of patients. As new clinical techniques are introduced, it would seem logic to preclinically validate them against this experimental standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 73 publications
(227 reference statements)
0
30
0
Order By: Relevance
“…This led to the concept of fetal intervention to arrest or reverse the natural history. Successful fetal coverage of SBA with improved functional outcome was first demonstrated in the SBA fetal lamb model 22. This was translated clinically with encouraging early results in several small case series 23–25.…”
Section: Introduction and Rationalementioning
confidence: 92%
See 1 more Smart Citation
“…This led to the concept of fetal intervention to arrest or reverse the natural history. Successful fetal coverage of SBA with improved functional outcome was first demonstrated in the SBA fetal lamb model 22. This was translated clinically with encouraging early results in several small case series 23–25.…”
Section: Introduction and Rationalementioning
confidence: 92%
“…Further technical development was put on hold in the USA by a historic national agreement of the leading fetal therapy centres in support of the MOMS. Based on the results of this trial yet without much experimental evidence,22 many centres recently opened and started fetoscopic programmes. Outcomes on more than 200 fetoscopic SBA repairs are currently reported (table 4).…”
Section: Fetoscopic Surgery For Sbamentioning
confidence: 99%
“…Animal models of spina bifida have suggested that open fetal repair is safe and effective . The first open fetal spina bifida repair in humans was performed in 1998 and, over the following 5 years, several observational studies were published with generally encouraging results.…”
Section: Open Fetal Repair Of Spina Bifidamentioning
confidence: 99%
“…The debate concerning the optimal surgical approach for fetoscopic MMC repair is ongoing, as discussed in several recent papers on this subject, and is thus not the focus of this review . However, optimization of the PACI technique may also influence clinical outcomes and is potentially relevant to other surgeries, such as fetoscopic laser coagulation …”
Section: Fetal Surgery For Myelomeningocelementioning
confidence: 99%
“…9 The debate concerning the optimal surgical approach for fetoscopic MMC repair is ongoing, as discussed in several recent papers on this subject, and is thus not the focus of this review. 25,[27][28][29] However, optimization of the PACI technique may also influence clinical outcomes and is potentially relevant to other surgeries, such as fetoscopic laser coagulation. 30 3 | CARBON DIOXIDE PHYSIOLOGY CO 2 is a highly soluble by product of aerobic cellular metabolism that rapidly diffuses from tissues into the blood (Figure 1).…”
Section: Fetal Surgery For Myelomeningocelementioning
confidence: 99%